Active brownian particles propelled by sound - Kaya, Serhat. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
Small particles in acoustic elds experience the so-called acoustic radiation forces by which the motion of particles can be manipulated in a contact-less way. Active Brownian particles have the ability to propel themselves by converting ambient energy into kinetic energy. However, because of the lack of study, the behavior of active Brownian particles in vicinity of external elds is not well-understood. The usage of acoustic elds in controlling the motion of these particles was suggested before, but this e ect has not been resolved analytically yet. In the analysis contained herein, the behavior of active particles inside an acoustic eld is investigated by constructing the equation of motion for a single particle. This is the rst time in the literature whereby the analytic form of the acoustic radiation forces is integrated with the dynamic equations of the system. The resulting equation is solved via numerical techniques. Then, with the performed simulations for two di erent active matter models, the collective behavior of active Brownian particles is also exploited.
Keywords: Acoustic imaging.; Brownian motion processes.